A Comparison of Seasonal Reproductive Pattern in Two Sympatric Darters of the Simoperca Clade, Etheostoma duryi and Etheostoma simoterum - Tiffany Bell; Elizabeth Cantrell; Bruce Stallsmith (Southeastern Fishes Council Proceedings, 2022)
We present results from an examination of the seasonal reproductive patterns of two closely related sympatric darter species of the Simoperca clade, Etheostoma duryi and Etheostoma simoterum. Most members of the genus Etheostoma exhibit striking sexual dimorphism, making reproductive strategy a logical point of study. Monthly collections of specimens over a one-year period were performed at a single site on the Flint River near Huntsville, Alabama. Standard length and gross somatic mass were measured for all individuals. Sex ratio was examined for possible skew. Measures of reproductive effort were monthly means of gonadosomatic index of both sexes, total oocyte count, oocyte size at different development stages, and clutch size. Reproductive season for both species was February through May. Etheostoma duryi was found to be slightly larger in SL and mass, and to produce more oocytes, larger clutch size, and smaller oocytes earlier in the breeding season. Both species displayed strong female skew, especially Etheostoma simoterum.
Keywords: sexual dimorphism; female skew; gonadosomatic index; clutch size; percidae